ESTUDIO EXPLORATORIO DE LAS INTERACCIONES MENTALES DE LOS ESTUDIANTES DE SEXTO GRADO SOBRE EL ENTENDIMIENTO CONCEPTUAL DE MULTIPLICACIÓN1 - Figueroa Molina, Roberto; Utria Echeverría, Carlos; Colpas Castillo, Rafael; Araújo Pereira, Antonio (Tecné, Episteme y Didaxis: TED, 2004)
This work constitutes a descriptive case análisis intended to explore how students of mathematical sixth grade build and internalize the concept of multiplication from their beginanig in the formal education. It olso reviews the process they apply to elaborate their real multiplication concept.